International Solidarity Fund : inter-departmental correspondence (copy) - Tewson, Vincent
028-0192-001 H. V. Tewson. Secretary's. Sir Walter Citrine. 5th November, 1936. INTERNATIONAL SOLIDARITY FUND. In again perusing the report of the delegation to Spain (copy attached) I would draw your particular attention to pages 3 and 4 which I have marked. From this it is quite clear that the list of necessities has been agreed upon and I think we should make a strong point on Friday morning of ascertaining whether these goods have been sent. It is clear from the report that if very little has been done it is not the responsibility of the Committee in Spain, but purely that of the International Joint Committee. 292/946/28/192